Peluang dan Tantangan Bank Syari’ah di Indonesia dalam Era Globalisasi - Zaenal Arifin; Maman Suparman; Andi Achmad Zulkarnaen (Sekolah Tinggi Ilmu Hukum (STIH) Prof Gayus Lumbuun, 2024)
Since enforcement of Law No. 7, 1992, the Syariah Bank started in knowing by Indonesian society and more developed by Law no. 10, 1998. so that there are two kinds of banking principles in this country, that is the conventional banking principle and the Syariah banking principle. The difference of both, in transaction of credit, the Syariah Bank doest not pick up interest from debitor or customer. We may say, from where or what is return for the Syariah Bank? The return is produced by cooperation between creditor (The Syariah Bank) with debtor or customer comprising of mudharabah, that is financing based on principle of income sharing; financing based on capital participation (musharakah); the principle of sale and purchase in goods which gets fortune (murabahah); financing of goods capital based on pure hire without option (ijarah) or in option to transfer ownership of hired goods/property from party of banker to the other party (ijarah wa igtina). Thus, there are dualistic banking principles in Indonesia Nonetheless, contradiction is none. Its sphere is freedom of choice for customers in accordance with their like without prohibition by governing legislation.